Estudio comparativo de variedades del camote (Ipomoea batatas) para determinar su empleo en la industria de alimentos - Cereda, M.P; Conceiçao, F.A.D; Cagliari, A.M; Heezen, A.M; Fioretto, R.A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
A comparative study of sweet potatoe varieties was conducted to estimate their utilization in food industry. Eighteen varieties were utilized in this study including varieties with pupl of different color (cream, orange and purple). The orange varieties were the most important to the food industries. After harvesting, the material was analyzed for color of the pulp, dry weight, starch, α and β amylases, enzhnatic browning, Brix of the crude and boiled broth, pH of the crude broth, viscosity of the boiled paste and general aspects. ft is concluded that some varieties have better chance for processing than others in the food industry.